Pengaruh Rotasi Kantor Akuntan Publik dan Rotasi Akuntan Publik (Partner Auditor) terhadap Kualitas Audit (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013) - Adhi Perdana, Muhammad; Juliarto, Agung (Diponegoro Journal of Accounting, 2014)
The objective of this research is to analyze the effect of rotation of audit firm (KAP) and rotation audit partner (PA) on the audit quality. Audit quality is measured using discretionary accruals. This research is based on previous research conducted by Siregar et al (2011). The sample of this research was manufacturing company which listed on the Indonesian Stock Exchange (BEI) in the year 2010 to 2013. Data were collected by using purposive sampling method and 298 observation data were analyzed. This study utilized linier regression as a main analysis tool. The results of multiple regression analysis show that the rotation of audit firm has a significant positive effect on audit quality. While, the rotation of auditor partner has no a significant effect on audit quality.